Feasibility Study Of Religion Tourism Business For The Young People - Lailatul, Apriliana; Melinda, Tina (TRIKONOMIKA, 2018)
The goal of the research is to find out the feasibility of the development of the travel service business and backpacker Umrah Easy Trip that was developed by young people. It is reviewed based on five aspects of business feasibility study including: market aspect, legal aspect, technical and technological aspect, management aspect and financial aspect. A qualitative approach is used in this study by using the interview. Five interviewees consisting of three owners of backpacker Umrah service and two consumers of backpacker Umrah. Result of the study mentioned that the business of backpacker Umrah is reasonable to be run and developed if it is reviewed of the five aspects of the business feasibility study, namely: market aspect, legal aspect, technical aspect and technological aspect, management aspect and financial aspect. Easy Trip should learn from business owners who already ran the backpacker Umrah to develop backpacker Umrah who has already pioneered.